ANALISA SEKSISME LINGUISTIK TERBUKA PADA DIALOG PEREMPUAN DALAM FILM “10 THINGS I HATE ABOUT YOU, (500) DAYS OF SUMMER, DAN SUPERBAD ” - Sihite, Manda Chrisencia; Wibowo, Kunto Adi; Rahmawan, Detta (Center for Gender and Child Studies (Pusat Studi Gender dan Anak) LP2M UIN Syarif Hidayatullah Jakarta, 2024)
Abstract. This study analyzes sexist dialogue directed at female characters in romantic comedy films using a quantitative content analysis method. The research was conducted on three romantic comedies: